Forbidden promises - Williams, Synithia (Williams, Synithia. Jackson Falls., 2020)
Get in and get out. That was India Robidoux<U+2019>s plan for this family visit. But when her brother needs her help with his high-profile political campaign, India has no choice but to stay and face the one man she<U+2019>s been running from for years- Travis, her sister<U+2019>s ex-husband. One hot summer night when Travis was still free, they celebrated her birthday with whiskey and an unforgettable kiss. The memory is as strong as ever- and so are the feelings she<U+2019>s tried so hard to forget. Travis Strickland owes everything to the Robidoux family. There<U+2019>s nothing he wouldn<U+2019>t do for them- his divorce could never change that. Still, he has one regret. Impulsive and passionate, India always understood him better than anyone else. And the longer they work together on the campaign, the more torn he is. Coming between her and her sister is out of the question. But how can he let love pass him by a second time?